The return to foreign aid - Carl-Johan Dalgaard; Henrik Hansen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We investigate the marginal productivity of investment across countries. The aim is to estimate the return on investments financed by foreign aid and by domestic resource mobilization, using aggregate data. Both returns are expected to vary across countries and time. Consequently we develop a correlated random coefficients model, to estimate the average aggregate return on 'aid investments' and 'domestic investments'. Across different estimators and two different sources for GDP and investment data our findings are remarkably robust; the average gross return on 'aid investments' is about 20 per cent. This is in accord with micro estimates of the economic rate of return.
Keywords: C23; F35; O47; 330; productivity; growth accounting; foreign aid; random coefficients; panel data